ChemInform Abstract: A Concise Total Synthesis of Cleistenolide. Issue 48 (10th November 2016) - Reddy, A. Bal; Kumara Swamy, B.; Yadav, Jhillu Singh
Abstract: Cleistenolide (I) is obtained in 42.5% overall yield over six steps starting from D‐glucose diacetonide using a selective benzoylation and Still—Gennari olefination as key steps.